Theoretical wave description in undulatory swimming - a new multi-dimensional approach - Hochstein, S.; Buschhorn, M.; Blickhan, R. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Undulatory underwater swimming (UUS) is of great importance to sport swimming due to its application after the start and turn. Thereby, muscular power generates waves that propagate along the body in a pedal direction. As this 3-dimensional body wave propagates through swimmerfs body (with time), the individul body segments accelerate the surrounding water against the direction of swimming. To substantiate the results and to compare different swimmers, various visualization methods were used, however only using 2-dimensional views (either kick amplitude over time at a fixed location or the kick amplitude over swimming direction at a fixed time). However, no representation exists that simultaneously illustrates information about a variety of significant variables of motion while visualizing the shape of the motion over the time.